2019
DOI: 10.1007/s00018-018-3000-z
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA in stem cell pluripotency and lineage commitment: functions and evolutionary conservation

Abstract: LncRNAs have recently emerged as new and fundamental transcriptional and post-transcriptional regulators acting at multiple levels of gene expression. Indeed, lncRNAs participate in a wide variety of stem cell and developmental processes, acting in cis and/or in trans in the nuclear and/or in the cytoplasmic compartments, and generating an intricate network of interactions with RNAs, enhancers, and chromatin-modifier complexes. Given the versatility of these molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 128 publications
(141 reference statements)
1
64
0
5
Order By: Relevance
“…MiRNAs directly affect HIF-1α expression and activity, while others may have indirect regulations. LncRNAs have diverse regulatory functions, which can modulate chromatin remodeling, transcriptional regulation, posttranscriptional processing, and translation [98,99]. Emerging reports have suggested the function of lncRNAs as competing endogenous RNAs (ceRNAs) for miRNAs to regulate related mRNA expression at the posttranscriptional level [100], including HIF-1α mRNA.…”
Section: Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…MiRNAs directly affect HIF-1α expression and activity, while others may have indirect regulations. LncRNAs have diverse regulatory functions, which can modulate chromatin remodeling, transcriptional regulation, posttranscriptional processing, and translation [98,99]. Emerging reports have suggested the function of lncRNAs as competing endogenous RNAs (ceRNAs) for miRNAs to regulate related mRNA expression at the posttranscriptional level [100], including HIF-1α mRNA.…”
Section: Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…ChIP-Seq was performed to generate a database to illustrate the relationship between transcription factors and lncRNAs in pluripotency regulation (Yang et al, 2013). Most lncRNAs were regulated by key pluripotent transcription factors, including Oct4, Sox2 and Nanog (Ng et al, 2012;Fico et al, 2019). Recently, Du and coauthors identified multiple pluripotency-associated lncRNAs embedded in the chromatin regulatory network by combining RNA-Seq and RAT-seq (Du et al, 2018).…”
Section: The Role Of Lncrna In Stem Cell Pluripotencymentioning
confidence: 99%
“…Long ncRNAs have diversity of regulatory functions, which can modulate chromatin remodelling, transcriptional regulation and post‐transcriptional processing, translation 74,75 . Although multiple functions of lncRNAs have been observed, competing endogenous RNA (ceRNA) or miRNA sponge is the most focused function.…”
Section: Long Non‐coding Rnasmentioning
confidence: 99%